2000
DOI: 10.1002/1521-4184(200011)333:11<365::aid-ardp365>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activity of Some New Quinazoline and Benzoxazinone Derivatives

Abstract: The hitherto unknown 2‐isopropyl‐6,8‐dibromo‐4H‐3,1‐benzoxazin‐4‐one (2) was subjected to condensation with either primary or secondary amines affording the benzamide derivatives (3—7), while with alcohols in presence of the base, corresponding esters were obtained (8 and 9). Acylation of the hydrazide (12) or its cyclized form (13) gave (14—17). The quinazolinone derivative (18) was obtained either when (12) was reacted with nitrous acid or via fusion of (2) with ammonium acetate. The thione (20) which was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…For related literature, see: Allen et al (1987); Bain & Smalley (1968); Bernstein et al (1995); Bouillant et al (1983); Colson et al (2005); El-Din (2000); Fenton et al (1989); Francis et al (2000); Gutschow et al (1998); Hamprecht et al (2004); Hauteville et al (1988); Hodson et al (2000); Johnson & Pattison (1986); Kakuta et al (2001); Krantz et al (1990); Mayama et al (1981); Pavlidis & Perry (1994); Ponchet et al (1984); Shalaby et al (2000); Ulrich (1991); Uejima et al (1993). Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For related literature, see: Allen et al (1987); Bain & Smalley (1968); Bernstein et al (1995); Bouillant et al (1983); Colson et al (2005); El-Din (2000); Fenton et al (1989); Francis et al (2000); Gutschow et al (1998); Hamprecht et al (2004); Hauteville et al (1988); Hodson et al (2000); Johnson & Pattison (1986); Kakuta et al (2001); Krantz et al (1990); Mayama et al (1981); Pavlidis & Perry (1994); Ponchet et al (1984); Shalaby et al (2000); Ulrich (1991); Uejima et al (1993). Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…Initial studies on 2-substituted-4H-3,1-benzoxazin-4-one showed good cytotoxic activity (Pavlidis & Perry, 1994) and herbicidal properties (Hamprecht et al, 2004). A variety of biological activities were associated with 2-Substituted-4H-3,1-benzoxazin-4-ones for example antifungal, antibacterial (Bouillant et al, 1983;Ponchet et al, 1984;Mayama et al, 1981;Hauteville et al, 1988;El-Din, 2000;Shalaby et al, 2000) and anti-elastase properties (Colson et al, 2005). They can be used for the treatment of obesity (Hodson et al, 2000) and also found to be novel specific puromycin-sensitive aminopeptidase inhibitors (Kakuta et al, 2001).…”
Section: Related Literaturementioning
confidence: 99%
“…The 4-ethylthio-6-fluoroquinazoline had potent antifungal activities against practically all the tested fungi (Gibberella zeae, Fusarium oxysporum, Cardamine mandshurica, Rhizoctonia solani, Thanatephorus cucumeris, Phytophthora infestans, Sclerotinia sclerotiorum, Botrytis cinerea, Colletotrichum gloeosporioides) and showed a broad-spectrum bioactivity 9 . Also quinazoline-4(3H)-thione's derivatives possessed antifungal properties against Sclerotium cepivorum and Botrytis allii 10 . Even bis-quinazolines showed antimicrobial activity 11 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Particularly, benzoxazine derivatives display various biological activities such as anticancer, 2 antimicrobial, 3 antifungal, 4 and antiplatete 5 activities. As part of an ongoing medicinal chemistry program on anti-tuberculosis drug discovery, 1,3-benzoxazin-4-one motif has attracted our considerable interest.…”
Section: Introductionmentioning
confidence: 99%